The Gap Between the Required Entry-Level Job Experience and the Opportunity for the Freshers in Bangladesh - Sultana, Azmery (Social Sciences and Development Review, 2022)
Proper utilization of human capital is one of the most important issues in the developing economy of a country. The paper investigates the impact of the gap between the required job experience for entry-level and the remaining job opportunity for the freshers of Bangladesh. To conduct the research, participants from different sectors such as students, entry-level, mid-level, and freshers have been chosen for data collection. The collected information was solicited on the current gap between the required entry level job experience and the fresher’s job opportunity in Bangladesh. The performance construct was defined by the term’s effectiveness, required experience level, knowledge gap, current job status, minimum years of required experience, flexibility, the opportunity of getting a job, fresher’s depression level, and unemployment rate. The collected data were analyzed through descriptive statistics. For example, several people from different levels from the job holders to the students have participated here. The data shows a worse contribution of the required level of experience for getting into a job for the freshers. A minimum year of experience is required for getting into the job but on the other hand, freshers are not getting any opportunity to implement their knowledge in the practical field. The absence of opportunity has risen the unemployment rate in Bangladesh. Around 80% of the participants of the survey have admitted that the required level of experience is the main reason for the freshers not getting into the job after completing their graduation (Billett, 2008). A better implementation opportunity of the acquired knowledge is one of the most significant ways of getting out of this problem.
Keywords: entry-level job experience; current status; frustration; knowledge gap; insufficient opportunity; depression of the freshers; flexibility; unemployment rate